Onboarding Model to Integrate Newcomers into Scrum Team at an Insurance Company - Pramudya Mahardhika; Eko K. Budiardjo; Kodrat Mahatma; Shinta Dewi Larasati (Jurnal Sistem Informasi, 2024)
PT XYZ applies the Scrum framework to meet application’s user demands quickly. The average percentage of IT employee turnover that occurred at PT XYZ from 2020 to 2022 was 14.5%. Every time a company recruits a new employee, the company must help that employee to adapt the Scrum method used for the company's system development process. However, PT XYZ information technology division does not yet have a specific onboarding method to help new employees adapt to the implementation of Scrum effectively without disrupting the ongoing sprint. Qualitative methods are used in the case study to collect data from a hybrid working Scrum team through interviews. The interview data was analyzed thematically with a determined model from an existing onboarding theory. Onboarding practices and adjustments are described and delivered consisting of onboarding activities, newcomer adjustments, and workplace adjustments. A combination of general and specific onboarding practices related to agile helps the successful onboarding of new members to a Scrum team. A practical guide is also described to improve successful onboarding practices into Scrum teams.